Becoming a Woman: The Overflow of the Modern Transcendental Project into Women’s Monstrous Experience - García Ortiz, Doris Lised (Universidad Distrital Francisco José de Caldas, 2020)
The article presents an ontological and political approach to the category of becoming a woman in modernity, debating between different academic perspectives of philosophy and history, with the aim of providing elements of analysis that contribute to the understanding of women in the field of social studies. It is about building a theoretical and practical input on production forms of female bodies from cultural, political and social locations, as well, as an approach to the processes of women resistance to these naturalized positions, deterritorializing the ways in which they have been named and disciplined from the hegemonic masculine knowledge. In this sense, it is intended to trace the monstrous events of women, detaching this analysis from essentialist views of being a woman and, on the other side, providing elements to understand women’s singular and strange expression from an incarnated materialism.